1992
DOI: 10.1111/j.1540-5915.1992.tb00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Forecasting: Some Implementation Guidelines

Abstract: Constrained forecasting has become a popular approach to the complex task of predicting future sales. Mixed performance results have been obtained by companies employing constrained forecasting systems software packages which probably reflects the lack of any clear system implementation guidelines. A number of important operational parameters such as the number of product families, criterion used to define product families, number of system levels, etc. must be specified. This study reports on an investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 10 publications
2
21
0
Order By: Relevance
“…There is also an increasing number of investigations into forecasting approaches which derive item forecasts from a forecast for a family of items. For example, Fliedner and Mabert [8] examined two hierarchical forecasting system parameters: (1) family group size and (2) criteria used to identify components of families. They found that the size of family groups (the number of component items) is not of great importance but the homogeneity of parent groups (correlation among group members) seemed important, although no indication of the direction of this effect was provided.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also an increasing number of investigations into forecasting approaches which derive item forecasts from a forecast for a family of items. For example, Fliedner and Mabert [8] examined two hierarchical forecasting system parameters: (1) family group size and (2) criteria used to identify components of families. They found that the size of family groups (the number of component items) is not of great importance but the homogeneity of parent groups (correlation among group members) seemed important, although no indication of the direction of this effect was provided.…”
Section: Introductionmentioning
confidence: 99%
“…Fliedner and Mabert [8] examined three factor level settings of family size and four criteria for identifying family group members. This investigation utilizes similar settings of family size and volume-based methods for family member identification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grouping criteria Volume and dollar-volume: ↑TDF Empirical study Automotive spare parts Fliedner and Mabert (1992) ψ = the portion of the unsatisfied demand for an item that is passed to another item within a group; ↓ (or ↑) = decreasing (or increasing) the value of the demand feature increases the relative performance of the forecasting strategy; TDF = top-down forecasting; DF = direct forecasting; CF = combinatorial forecasting; dollar-volume = demand per period×item price.…”
Section: Demand Featuresmentioning
confidence: 99%
“…Miller et al (1976) demonstrated that forecast performance is dependent upon the following factors: (1) the magnitude of the correlation between the disaggregate forecast variables; (2) the magnitude of the correlation between the forecast errors of disaggregate variables; and (3) the quality of the forecasting techniques. Fliedner and Mabert (1992) examined two factors (family size and family grouping criteria) that are relevant to the design of HF systems. In particular, performance contrasts of HF systems utilizing different family sizes and family grouping criteria were conducted using a traditional, short-term forecast method.…”
Section: Introductionmentioning
confidence: 99%